The development of nickel-based heterogeneous catalysts with ultrasonic irradiation for the hydrogenation of plant-based feedstock - Lim, Mitchell Shyan Wei (2022)
Nickel-based heterogeneous catalysts are characterised by their widespread utilisation in the hydrogenation of fats and oleochemicals. Nevertheless, various aspects of the catalyst are still in continuous development and improvement. Therefore, bridging these knowledge gaps concerning the functionality of the catalyst motivated the investigations constituting this thesis.